Profunda Brachii Pseudoaneurysm following Supracondylar Fracture of Humerus Repair in an 8-Year-Old Boy: A Case Report and Review of Literature - Hamed Ghoddusi Johari (Hindawi Limited, 2021)
Arterial pseudoaneurysm can manifest in almost all arteries, but peripheral ones such as brachial artery pseudoaneurysm are rare and typically happen after trauma or infections. We describe an 8-year-old boy who presented with a large nonpulsatile soft tissue mass-like lesion 20 days after supracondylar fracture of the humerus which was fixed using Kirschner wire. The neurovascular examination was normal; CT angiography revealed a large pseudoaneurysm arising from the left profunda brachii artery. The patient went under surgical repair and was discharged from the hospital with an uneventful postop course. A high index of suspicion is necessary in cases with humeral fractures for the early diagnosis of pseudoaneurysm where the delayed diagnosis may cause fatal outcomes.